Application of decomposed theory of planned behavior on internet banking adoption in Jordan - Al-Majali, Malek; Nik Mat, Nik Kamariah (Array Development, 2010)
This study investigates twelve factors that may influence internet banking adoption in Jordan. Using of DTPB (Decomposed Theory of Planned Behavior) model in this study provide a comprehensive model to understand the antecedents of Internet Banking Adoption in Jordan. The results show that all hypotheses were supported except for two hypotheses related to compatibility and technology support.